2013
DOI: 10.3390/nu5010283
|View full text |Cite
|
Sign up to set email alerts
|

Food Sources of Energy and Nutrients among Children in the United States: National Health and Nutrition Examination Survey 2003–2006

Abstract: Background: Recent detailed analyses of data on dietary sources of energy and nutrients in US children are lacking. The objective of this study was to identify food sources of energy and 28 nutrients for children in the United States. Methods: Analyses of food sources were conducted using a single 24-h recall collected from children 2 to 18 years old (n = 7332) in the 2003–2006 National Health and Nutrition Examination Survey. Sources of nutrients contained in foods were determined using nutrient composition d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
137
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(151 citation statements)
references
References 41 publications
9
137
1
4
Order By: Relevance
“…49 Keast et al reported that fruits were the major contributor (10.4%) to American children's dietary fiber intake. 50 Increasing the proportion of fruit that is eaten as whole, rather than as juice, can help all Americans consume more fiber. In addition, beans (legumes) and peas, other vegetables, whole grain foods, and nuts are good sources of dietary fiber.…”
Section: Discussionmentioning
confidence: 99%
“…49 Keast et al reported that fruits were the major contributor (10.4%) to American children's dietary fiber intake. 50 Increasing the proportion of fruit that is eaten as whole, rather than as juice, can help all Americans consume more fiber. In addition, beans (legumes) and peas, other vegetables, whole grain foods, and nuts are good sources of dietary fiber.…”
Section: Discussionmentioning
confidence: 99%
“…Meeting dairy recommendations had less impact on vitamin D and potassium adequacy of the diet. While milk contributes the most of these two nutrients to the U.S. diet compared to other foods and beverages, 3,4 the data indicate that increasing a single food group will not be sufficient to meet recommended vitamin D and potassium intake based on current diet patterns, and additional dietary strategies would be needed. As has been noted by the Institute of Medicine, 9 the most appropriate measure of vitamin D adequacy is serum 25-hydroxyvitamin D to take into account the contributions from both sunlight and diet.…”
Section: Other Vitamins and Mineralsmentioning
confidence: 99%
“…Dietary interventions to ensure males consume sufficient vitamin A should therefore be explored. This could include recommending four servings of low-fat dairy foods for males, particularly milk as NHANES consumption data indicates it is also the leading food source of vitamin A for children 3 and adults 4 in the U.S, as well as increasing intake of orange and dark green vegetables which are rich sources of vitamin A.…”
Section: Other Vitamins and Mineralsmentioning
confidence: 99%
“…However, apart from the aforementioned restrictions, no manufacturer provides instructions about the type of beverages that can be consumed. Considering the widespread consumption of acidic soft drinks, such as sodas, fruit juices and ice teas, and especially among children and adolescents, 18 a better understanding of fluoride release from FV under acidic conditions is warranted. Hence, the aim of the present in vitro study was to investigate the in vitro fluoride release from fluoride varnishes under mild and strong acidic conditions.…”
Section: Introductionmentioning
confidence: 99%